Exploring the effects of perfluorooctanoic acid (PFOA) and tetrabromobisphenol A (TBBP-A) on silkworm from the insights of metabolome - Xing Zhang; Yifei Kong; Zihan He; Wenbin Yu; Wenjing Shao; Chengliang Gong; Wenlin Zhou; Xiaolong Hu (Ecotoxicology and Environmental Safety)
Perfluorooctanoic acid (PFOA) and tetrabromobisphenol A (TBBP-A) are emerging environmental contaminants with recognized potential health and ecological risks. This study investigated the effects of PFOA and TBBP-A exposure on the global of metabolites of silkworm gut with GC-MS metabolomics. Our results revealed distinct metabolic alterations in silkworms exposed to PFOA and TBBP-A, highlighting their differential impacts on silkworm health and productivity. Exposure to these chemicals significantly altered metabolic profiles, leading to disruptions in pathways related to lipid, carbohydrate, and amino acid metabolism. These findings suggest that PFOA and TBBP-A disrupt crucial metabolic processes in silkworms, indicating potential toxicity and prompting further investigation into their effects on human health and the environment. Ongoing research is crucial to develop safer alternatives and mitigate the risks associated with these persistent contaminants.